Pengaruh Struktur Modal terhadap Kinerja Keuangan pada Perusahaan Sektor Industri Barang Konsumsi di BEI - Putu Yumi Chandra Dewi; Ida Bagus Panji Sedana (Universitas Veteran Bangun Nusantara, 2024)
Financial performance is an analysis conducted to see the extent to which a company has carried out using the rules of financial implementation properly and correctly. In improving the performance and value of the company, consideration of decisions regarding capital structure plays a very important and crucial role. This study aims to determine the effect of capital structure proxied by DAR and DER ratios on the company's financial performance proxied by ROE ratio. The population used in this study are consumer goods industry sector companies listed on the Indonesia Stock Exchange during the observation year 2018-2022. A sample of five companies was found using purposive sampling method with a research period of five years so that twenty-five observations were obtained. The data analysis technique used in this research is the Multiple Linear Regression Test. The results showed that DAR had a negative and significant effect on ROE and DER had a positive and significant effect on ROE. The theoretical research implication is that research can strengthen the results of further research to add to empirical studies and science, especially DAR and DER on ROE. The practical implication of research is the contribution of this research in helping company management as material for evaluating financial performance, especially regarding DAR, DER, and ROE and as a consideration in formulating financial policies.